Development of ecological competence of the person in the conditions of «ekology-psychology» interactions of the future experts: the general conclusions of theoretical and empirical research - A V Gagarin (Peoples' Friendship University of Russia (RUDN University), 2010)
This article is the third, final publications in a series, devoted to a problem of development of ecological competence of the person in «ecology-psychological» interactions of the future experts [4; 5]; includes the general conclusions by results of theoretical and empirical research of the specified problem.